Synaptic mutant huntingtin inhibits synapsin-1 phosphorylation and causes neurological symptoms - Xu, Qiaoqiao (The Rockefeller University Press, 2013)
Many genetic mouse models of Huntington’s disease (HD) have established that mutant huntingtin (htt) accumulates in various subcellular regions to affect a variety of cellular functions, but whether and how synaptic mutant htt directly mediates HD neuropathology remains to be determined. We generated transgenic mice that selectively express mutant htt in the presynaptic terminals. Although it was not overexpressed, synaptic mutant htt caused age-dependent neurological symptoms and early death in mice as well as defects in synaptic neurotransmitter release. Mass spectrometry analysis of synaptic fractions and immunoprecipitation of synapsin-1 from HD CAG150 knockin mouse brains revealed that mutant htt binds to synapsin-1, a protein whose phosphorylation is critical for neurotransmitter release. We found that polyglutamine-expanded exon1 htt binds to the C-terminal region of synapsin-1 to reduce synapsin-1 phosphorylation. Our findings point to a critical role for synaptic htt in the neurological symptoms of HD, providing a new therapeutic target.